The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1742-6596/1529/2/022031
|View full text |Cite
|
Sign up to set email alerts
|

Potential acoustic treatment analysis using sabine formula in unoccupied classroom

Abstract: Effective teaching and learning, not only taking into account the good teaching methodology and facilities but the acoustic level in the classroom should also be addressed. RT-60 is the time required for sound decay in a classroom. The time taken for the sound to decay depends on the absorption coefficients (α) of surface material and the volume of the room. This paper aims to identify potential treatment materials for improving the value of RT-60 of the selected unoccupied teaching hall/classroom at one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The detailed configuration for surface treatments is presented in Table 2. In a prior investigation conducted by Abdullah et al (2020), the ODEON software was utilized to implement acoustic improvements in university classrooms located in Malaysia. The simulation incorporates gypsum board and perforated plywood as materials for treating the walls and ceilings.…”
Section: Simulation Work For Acoustics Treatment Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed configuration for surface treatments is presented in Table 2. In a prior investigation conducted by Abdullah et al (2020), the ODEON software was utilized to implement acoustic improvements in university classrooms located in Malaysia. The simulation incorporates gypsum board and perforated plywood as materials for treating the walls and ceilings.…”
Section: Simulation Work For Acoustics Treatment Alternativesmentioning
confidence: 99%
“…As mentioned by Acoustical Society of America ( 2000), installing a new lay-in ceiling suspended from the original ceiling is one of the treatments that can reduce the RT to desirable condition. In addition, the simulation method demonstrated that optimal RT conditions in classrooms can be attained by substituting reinforced concrete walls and microfiber ceilings with gypsum board and perforated plywood that is 12 mm thick (Abdullah et al, 2020). An adequate number of absorptive materials are required to be placed on the ceiling, walls, and floors to achieve a suitable RT for classrooms (Sundaravadhanan et al, 2017).…”
Section: Effects Of Surface Treatment On Reverberation Timementioning
confidence: 99%
“…The reverberation of a space has positive and negative aspects: in fact, if a certain value of the reverberation time helps to reinforce the direct sound it therefore improves listening; on the other hand, an excessive value of the sound tail compromises its quality [1,2]. For good reception, both in the case of speech and in the case of music, it is necessary to contain the decaying tail of reflected sound from a source and ensure a good spatial distribution of the sound field inside the room so that all listeners can perceive and appreciate the sound regardless of the space in which they are located [21].…”
Section: Reverberation Timementioning
confidence: 99%